Diversidad de criptógamas epífitas en dos tipos de bosque del parque Universitario de Educación Ambiental y recreación Francisco Vivar Castro, provincia de Loja. - Medina Benitez, Jefferson Vladimir (2018)
The neotropical montane forests are considered as hotspots of biodiversity, where epiphytic cryptogams are an important component related with ecosystem functioning, biomass and biodiversity. Lichens and bryophytes are very sensitive to environmental changes and they are indicators of forest quality. We evaluated the richness and composition of epiphytic cryptogams (bryophytes and lichens) in two different forest types (montane forests and mixed plantation of Juglans neotropica) of “Parque Universitario Francisco Vivar Castro”. In the present investigation, we realized 5 plots of 20 cm x 20 cm in each forest type, where registered presence/absence and coverage of epiphytic cryptogams on grids of 20 cm x 30 cm (100 phorophytes). We analyzed the effects of canopy cover and forest type on richness using generalized linear mixed model (GLMM). In addition, we analyzed changes in species composition with a non-metric multidimensional scaling (NMDS); and, a multivariate analysis of variance (PERMANOVA). We recorded a total of 135 species of epiphytes (55 bryophytes and 80 lichens). We found that richness and composition of species were influenced by forest type related with changes in light availability. Keywords: Montane forest; bryophytes, canopy cover, diversity, lichens.